DIGITAL TO ANALOG CONVERTER DAC 0800 WITH PC-BASED - Dedy Erwan Kustianto; Ir. Irawan Nimara, MM (Jurnal Sistem Komputer, 2000)
Computer produces a digital signal output of logic "0" and "1". While electronicdevices typically use an analog signal as a voltage source that a certain amount.Electronic devices that require analog signals can be connected to a computer using adigital to analog converter circuit. Digital to analog converter is used to change thedigital signal into analogue signal.To be able to relate to the computer to analog converter circuit, an interface is needed.The interface is often used in design is a PPI PC 8255. because it is cheap and easy touse. Software on digital to analog converter circuits used to control the output voltageanalog signal in the form desired to fit. So, with the analog signal can be used byelectronic equipment.